Microbial Contamination of Raw Camel Milk and Potential Public Health Hazards Related to its Consumption - Iqbal, Muhammad Naeem; Ashraf, Asfa (PSM Microbiology, 2023)
The microbial flora of raw camel milk is varied and may contain pathogens that can spread to humans. Some of the major bacterial pathogens isolated from raw milk or related equipment have been found to exhibit antimicrobial resistance, which may have a substantial impact on public health. The contamination of raw camel milk with pathogens can arise from animals with systemic infection, localized infections such as mastitis, fecal contamination, and the farm environment. In this issue, Dogondaji et al. investigate the microbial content of raw camel milk obtained from five domesticated female camels. The incidence of Escherichia coli sub spp 0157:H7, Salmonella spp., and Staphylococcus aureus was reported in milk samples. A widespread inspection of hazard identification is necessary due to the wide range of possible microbiological risks associated with milk-producing animals. Consumers should be better informed about hazards and prevention strategies related to drinking raw milk, especially vulnerable/high-risk groups.